Required jacking force for deviation rectification of inclined structures supported with rigid piles - Chai, Shupeng; Fan, Liujun; Liang, Hui (Frontiers in Earth Science, 2022)
Light poles or transmission towers may become tilted over the design life, which needs rectifying considering safety and continued use. The jacking pushing method is an efficient way to rectify deviations of these inclined structures supported with rigid piles, but there is a lack of relevant engineering standards and research in this aspect. In this study, a numerical method using FLAC3D is proposed to estimate the required jacking force at the pile top to plumb inclined piles in cohesive soils. Good agreements between the results obtained from the present numerical models and those taken from published experimental and numerical results suggest the reliability of the conclusions. Besides, elaborate parameter analyses including pile geometry, soil properties, and properties of the soil-pile interface are conducted to investigate their influences on the required jacking force. The results can contribute to a safer and more cost-efficient design for rectifying deviations of rigid inclined piles, especially in terms of the required jacking force.